2006
DOI: 10.1080/08820130600745430
|View full text |Cite
|
Sign up to set email alerts
|

Hurdles to Lymphocyte Trafficking in the Tumor Microenvironment: Implications for Effective Immunotherapy

Abstract: An important consideration in the development of T cell-based cancer immunotherapy is that effector T cells must efficiently traffic to the tumor microenvironment in order to control malignant progression. T cell trafficking to target tissues is orchestrated by dynamic interactions between circulating lymphocytes and endothelial cells lining blood vessels. It is informative, in this regard, to compare and contrast the molecular mechanisms governing lymphocyte extravasation at distinct vascular sites: (1) high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 118 publications
3
60
0
Order By: Relevance
“…29 To our surprise, however, trafficking studies showed no differences in OT-1T cell recruitment or accumulation, when measured by absolute numbers in either PBS-or GCV-treated tumors. Levels of T-cell trafficking to tumors might be confounded by the fact that the number of T cells detected within tumors will be a balance between cell trafficking and cell death.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…29 To our surprise, however, trafficking studies showed no differences in OT-1T cell recruitment or accumulation, when measured by absolute numbers in either PBS-or GCV-treated tumors. Levels of T-cell trafficking to tumors might be confounded by the fact that the number of T cells detected within tumors will be a balance between cell trafficking and cell death.…”
Section: Discussionmentioning
confidence: 91%
“…First, the pro-inflammatory environment at the tumor site induced by HSVtk killing might serve as a potent means to attract more of the adoptively transferred antigen-specific T cells to the tumor, compared to tumors with no ongoing cell killing. 29 Alternatively, or additionally, the activated T cells, which reach the site of antigen expression at the tumor may be more active in terms of expression of effector functions such as perforin-mediated target cell lysis and interferon-g (IFN-g) expression. 28 Second, we recently delivered retroviral vectors encoding HSVtk to disseminated B16ova metastases by adsorbing retroviral particles to the surface of activated OT-1T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenic factors [vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF)] and immunosuppressive cytokines (transforming growth factor-h and IL-10) can mediate this effect by down-regulating endothelial adhesion molecules, such as intercellular adhesion molecule-1 and vascular cell adhesion molecule-1 (VCAM-1; ref. 39). Tumors from conventional MMTV/neu transgenic mice reportedly express both bFGF and VEGF but not VCAM-1 (16), which may account for the poor infiltration of some tumors in our model.…”
Section: Discussionmentioning
confidence: 99%
“…See Supplemental Methods for additional details. Briefly, 10 5 tumor cells were injected into surgically implanted dorsal skin flap single-sided window chambers (Research Instruments Inc.) (20,37). 14-21 days later, calcein-labeled T cells (2-10 × 10 7 cells/mouse) were gradually injected via the tail vein of anesthetized mice (1 mg/ml xylazine and 10 mg/ml ketamine; 10 ml/kg, i.p.)…”
Section: Figurementioning
confidence: 99%